Teacher Methods In The Perspective Of Islamic Education - Rinawati Hutabarat; Rizky Adinda (Proceeding International Seminar of Islamic Studies, 2019)
This study is entitled Methodes Teachers in Islamic Education Perspective, The problem that arises is that many teachers are less able to provide approaches in Islamic education, Are teachers less able to provide methods for educators, The process of Islamic education in its method has a very important position in efforts to achieve goals, because this becomes a means in the delivery of student material that is arranged in the curriculum without the method of a subject matter will not process ep efficiently and effectively in teaching and learning activities towards educational goals. The purpose of this research is to find out the methods of the Teachers in the Perspective of Islamic Education, the method used is Library Reserch, Qualitative it is found that there are many different kinds of approaches to Islamic education that can achieve the goals of Islamic education